The Correlation between Conservation Knowledge and Fisherman Perception about Mangrove Plantation Activities on Kampung Garapan, Desa Tanjung Pasir, Tangerang - Hadianti, Siti; Azrai, Eka Putri; Sukandar, Paskal (Biosfer: Jurnal Pendidikan Biologi, 2014)
Mangrove is a coastal ecosystem that has been severely damaged because of irresponsible people. One of the ways to overcome this problem is by carrying out mangrove plantation program. Conservation knowledge is important to form a good perception about the activity. This research was aimed to know the correlation between conservation knowledge and fisherman perception about mangrove plantation activity. It was held on Kampung Garapan, Desa Tanjung Pasir, Tangerang, Banten on June 2012 using a descriptive survey method of Correlation Study. A total of 40 fishermen were selected by simple random sampling. Instruments of conservation knowledge test and fisherman perception were used to obtain data. The mean score of conservation knowledge and fisherman perception were 81.75 and 69.02, respectively. Prerequisite test using normality test of kolmogorov-Smirnov showed a normal result while homogeneity test of F-test showed a non homogenous data. The Spearman Rank correlation coefficient was 0.049 showing a very weak correlation. As the result, it can be concluded that there was a correlation between conservation knowledge and fisherman perception about the mangrove plantation activities.